Suzdalevo Lake (Central Siberia, Russia)—A Tunguska Event-Related Impact Crater? - Kavková, Radana; Vondrák, Daniel; Chattová, Barbora; Svecova, Eva; Takac, Marian; Golias, Viktor; Štorc, Richard; Stanghellini, Carlo; Kletetschka, Gunther (Frontiers in Earth Science, 2022)
In 1908, a massive explosion known as the Tunguska Event (TE) occurred in Central Siberia. However, its origin remains widely discussed and environmental impacts are not known in detail. We investigated evidence of the TE in sediments of Suzdalevo Lake, which is located near the explosion epicenter. According to local nomads (Evenkis), Suzdalevo Lake did not exist before the TE and was considered as a possible impact-origin water body. However, apart from oral testimony, there is no evidence of the lake formation process. Two short sediment cores (SUZ1 and SUZ3) were retrieved from the lake and dated using 210Pb and 137Cs. The sedimentary record was characterized using magnetic susceptibility, X-ray fluorescence, and the screening for melted magnetic microspherules. To study possible effects of the TE on the lake ecosystem, we performed diatom and freshwater fauna remains analyses. Results indicate that the lake contains sediments that originated before the TE and thus its formation was not related to the impact. Also, the depth to diameter ratio of the lake basin is too low (<1/100) for a young impact crater. In one of the two cores (SUZ1), we documented distinct changes in the lake-catchment ecosystem that occurred within a 5-cm-thick depth interval calculated for the best fit depths for the year 1908 using three alternative age-depth models (CRS, CIC, CFCS), namely increases in terrestrial matter input (abundant fine plant macroremains, peaks in magnetic susceptibility and the Sr to Rb ratio) and taxonomic diversity and relative abundance of benthic taxa. The shifts in aquatic biota assemblages were likely caused by nutrient supply and improved water column mixing following a catchment disturbance. Nevertheless, precise timing of the observed abrupt changes in relation to the TE is not clear due to uncertainty of the 210Pb dating method and absence of melted magnetic microspherules or an event layer. The disturbance signals in the proxy data may postdate the TE. Our results demonstrate potential usefulness of the paleolimnological approach to understand the possible environmental consequences of the TE and similar events elsewhere.